Relationship between Body Mass Index (BMI) and Anemia Among Adolescent Indonesian Girls (Analysis of The Indonesia Family Life Survey 5th Data) - Rieza Enggardany; Lucia Yovita Hendrati; Noran Naqiah Hairi (Amerta Nutrition, 2021)
ABSTRACTBackground: Anemia is a condition characterized by low levels of hemoglobin (Hb) from normal limits. Anemia is still a public health problem. Data states that the prevalence of anemia in Indonesia in 2013 was 21.7%, with the number of sufferers known to be higher in women than men. The prevalence of anemia in the age range 15 to 24 years was 18.4%. Nutritional status shows the balance of nutrients due to the consumption, absorption, and use of nutrients that come from food in the body. A person's nutritional status can be said to be deficient if the body lacks intake of one or more essential nutrients for the body. One of the indicators for assessing a person's nutritional status is the Body Mass Index (BMI). Inadequate nutritional status will affect the nutritional status of iron in a person' s body so that it can be interpreted that nutritional status is one of the factors of anemia. Consuming foods with good nutritional value, especially foods that contain high iron will also affect the nutritional status of these adolescents so that the risk of suffering from anemia will decrease.Objective: This study aims to analyze the relationship between body mass index and anemia among young women in Indonesia.Methods: This study is a cross-sectional study. The data used are secondary data from the Indonesian Family Life Survey (IFLS) 5. The population of this study was all Indonesians who participated in IFLS 5. The sample used in this study amounted to 3,525 respondents. IInclusion criteria of this study included female, aged 10-18 years, unmarried, having complete data regarding body weight, height and hemoglobin measurement results. If data related to the measurement results of hemoglobin, body weight, height are incomplete, they will be excluded.The statistical test was used is a chi-square test.Results: There was a relationship between Body Mass Index (BMI) and anemia among young women in Indonesia (p = 0.034 <0.05).Based on the odd ratio analysis using the normal Body Mass Index (BMI) group as a comparison, it is known that young women with underweight BMI categories have a 1.198 greater risk of experiencing anemia than girls with normal BMI categories.Conclusion: There is a relationship between BMI and anemia in adolescent girls. It is important for young women to always pay attention to daily iron intake by eating foods that are rich in iron or taking blood-booster tablets (TTD) to avoid anemia.